Systematic Review of Chuna Manipulative Treatment for Ankle Sprain - Min Kyung Kwak; Min Wook Kim; Sang Jun Jeong; Shin Ae Kim; Mi Young Jeong; Jae Hong Kim (MEDrang Inc., 2018)
Background This study was performed to review the efficacy of national and international randomized controlled trials (RCT) investigating Chuna manipulative treatment for ankle sprains. Methods Online databases (PubMed, Cochrane, EMBASE, CNKI, NDSL, OASIS), were searched for studieswhere Chuna treatment was performed for ankle sprains up to October 12th, 2017. Only RCT were selectedthat fulfilled the inclusion/exclusion criteria. Data were analyzed using the Cochrane risk of bias tool. Results There were 676 studies retrieved from the databases, resulting in analysis of 24 RCT. There was an average of 7 treatment visits over a 7 day period and the most frequent evaluation tool used was efficacy rate,with drug therapy being the most common control used in the trials. In 15 RCT, several Chuna methods were used in combination, amongst which, the osteopathic technique was most common. Statistically significant improvement in evaluation indices was reported in 19 RCT, and in 3 RCT, statistically significant improvement was reported, but not for all indices. In the remaining 2 RCT, there were no significant differences in any of the evaluation indices. No adverse reactions were reported in any of the RCT, although it was book whether all the trial protocols indicated that adverse reactions should be monitored, and for this reason, the risk of bias was unclear. Conclusions The review of 24 studies suggest that Chuna manipulative treatment for ankle sprains waseffective in most cases, although, potential bias in these studies was difficult to evaluate.